From Risky Indebtedness to Long-Term PayLater Adoption: The Mediating Roles of Attitude, Usage, and Impulsive Buying - Rahmatin Sabila Rizqy; Arif Hartono (Yayasan Riset dan Pengembangan Intelektual, 2026)
The emergence of PayLater has brought significant changes to consumer consumption patterns, including the decision to adopt PayLater. This study expands the PayLater literature by exploring the impact of risky indebtedness behavior on long-term PayLater adoption. Unlike previous research, which predominantly examines PayLater as a trigger for financial distress, based on the theory of planned behavior, this study aims to analyze the role of risky indebtedness behavior and the mediating role of attitudes toward PayLater, PayLater use, and impulse buying on long-term PayLater adoption. Integrating behavioral factors into an adoption model can provide a more comprehensive understanding of consumer decision-making. Using a purposive sampling method, data from 256 Indonesian college students were obtained and analyzed using PLS-SEM. The results indicate a direct relationship between risky indebtedness behavior, attitudes toward PayLater, and PayLater use on long-term PayLater adoption. However, no direct relationship or mediating role was found for impulse buying. Practically, this study suggests that PayLater service providers should provide responsible lending practices and monitor consumer behavior to reduce excessive borrowing, while policymakers need to strengthen consumer financial literacy initiatives to avoid harmful lending practices.